Analisis SOAR Terhadap Strategi Keterbukaan Informasi Publik Melalui Pejabat Pengelola Informasi dan Dokumentasi Provinsi Jawa Timur - Annisa Ika Putri; Vidya Imanuari Pertiwi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
Public information disclosure is one of the principles of a state that guarantees the right of its people to access public information. Public information disclosure in Indonesia is contained in Law Number 14 of 2008. East Java Province is one of the provinces that implement public information disclosure. In providing public information, East Java Province has received several awards in the informative category. This paper aims to analyze and describe the public information disclosure strategy through the Information and Documentation Management Officer (PPID) of East Java Province using SOAR analysis. This research method uses qualitative with case study type. Data collection techniques were obtained through observation, interviews, and documentation. This paper uses primary data and secondary data. The results of this study indicate a public information disclosure strategy in East Java Province through PPID using SOAR analysis, namely, the strengths possessed by PPID East Java Province by coordinating and providing assistance to PPID implementing public agencies. Opportunities are utilized both internal opportunities derived from facilities and infrastructure and external opportunities by utilizing technological advances to develop websites as a forum for providing public information. Aspirations that are owned as the strength of PPID East Java Province, namely criticism and suggestions from leaders or other stakeholders regarding public information disclosure. The results of efforts through strategies carried out by the Public Information Management Officer in implementing public information disclosure services in East Java Province include the results of assistance, mentoring, and socialization efforts carried out by PPID.